2014
DOI: 10.1016/j.jclepro.2013.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Learning to change universities from within: a service-learning perspective on promoting sustainable consumption in higher education

Abstract: Learning to change universities from within: a service-learning perspective on promoting sustainable consumption in higher education

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
97
0
9

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 157 publications
(106 citation statements)
references
References 40 publications
0
97
0
9
Order By: Relevance
“…Lang (2012) and Barth (2014) come from the same institutional environment the Leuphana University of Luneburg, as do the rest of the authors of Barth (2014) andLang (2012) This should suggest a kind of "informer institution" quality.…”
Section: Cluster4mentioning
confidence: 91%
See 2 more Smart Citations
“…Lang (2012) and Barth (2014) come from the same institutional environment the Leuphana University of Luneburg, as do the rest of the authors of Barth (2014) andLang (2012) This should suggest a kind of "informer institution" quality.…”
Section: Cluster4mentioning
confidence: 91%
“…The betweenness centrality degree of the authors who are related to the articles analysed, is shown below: Table 4. Betweenness centrality degree Author/Article Betweenness centrality degree 24,3 19,0 Lang (2012) 6,3 Barth (2014) 3,3 Steiner (2006) 2,0…”
Section: Cluster4mentioning
confidence: 99%
See 1 more Smart Citation
“…In this way, students can develop competencies that enable them to solve complex sustainability-problems in their future careers. Examples of approaches integrating real-world issues are inter-and transdisciplinary project work, service-learning or research-based learning (with communities) (Barth et al, 2014;Lehmann et al, 2008;Thomas, 2009 for sustainability-driven entrepreneurship. Therefore, besides designing adequate contents, one major focus of the CASE project is to formulate an innovative, interand transdisciplinary pedagogical framework, focusing on the development of sustainability competencies in general and competencies for sustainability-driven entrepreneurship in particular.…”
Section: Competence-based Teaching and Learning In Higher Educationmentioning
confidence: 99%
“…As the chief executive of Universities UK, Nicola Dandridge, argues,'it's important to focus also on universities' wider and invaluable contribution to the green agenda in terms of their environment-related research and teaching' (People and Planet, 2011). Education for Sustainable Development is considered critical for altering values and behaviours of students and staff to move towards sustainable universities (Lozano, 2006), especially in the context of HEI carbon management (Barth et al, 2013;Williams and Kemp, 2013).…”
Section: Discussionmentioning
confidence: 99%